Evaluating The Usability of Three of The Lowermost Krg/Iraq University Websites in Webometrics Based on User Perspective - Abdulrahman, Ayub Othman; Hama Rawf, Karwan Mahdi; Gahfoor, Karzan Jaza (Science Journal of University of Zakho, 2022)
In the higher education sector, web based facilities perform a vital aspect to offer success of an academic institution, due to the users depend on the universities websites to achieve different academic instructions. Simultaneously, users may face many usability difficulties while having access to the websites. For that reason, this research investigates user based testing and questionnaires methods from user perspective to evaluate three of lowermost university websites in KRG/Iraq according to Ranking Web of Universities (webometrics); university of Raparin, university of Garmian, and university of Halabja. Thirty participants contribute to implementing six tasks of user-based methods and ten questions of questionnaire approach. Based on the analysing process, the accuracy of universities websites are; 86.7%, 79.5%, and 61.1% for each University of Raparin, University of Halabja, and University of Garmian respectively. Moreover, user satisfaction for the University of Raparin is 3.59, while 3.24 and 3.01 are the rates of satisfaction for University of Halabja and University of Garmian.
Keywords: Usability; Websites Usability; User Satisfaction; User Testing; Questionnaire; Usability criteria; Website Evaluation